(untitled) - Doff, Adrian (London, 1988)
This book contains detailed instructions for each training session. It includes transcripts of demonstrations, points of discussion with suggested answers, suggestions for organising activities, and master copies of visual material. It also contains all the Teacher's Workbook activities, apart from the 'Lesson preparation' sections. This book is in the form step-by-step instruction manual
Keywords: English language,English language,Tiếng Anh,Tiếng Anh; Study and teaching,Foreign speakers,Dạy và học,Nói tiếng nước ngoài